An experimental study of effect of atmospheric plasma treatment on shear strength of adhesively bonded GFRP-aluminum joints - AYAZ, Asil; OZDEMİR, Gizem Dilara and ERCAN, Utku Kurşat and SEVER, Kutlay and KORKUT, Nazik (International Journal of Computational and Experimental Science and Engineering, 2024)
The objective of this study is to investigate the effect of air (dielectric barrier discharge) DBD plasma treatment on the bonding strength of adhesively bonded glass fiber-reinforced epoxy composite-aluminum lap joints. The bonding performance of lap joints produced by the plasma treatment was compared with that of untreated and peel-ply surface treatments. Water contact angles of the substrates were measured for untreated, peel-ply, and plasma surface-treated substrates. Experimental results showed that plasma-treated aluminum and GFRP substrates increased the wettability properties and thus shear strength of adhesively bonded GFRP-Al joints increased. After the shear tests, the fracture surfaces of the substrates were visually examined and three different damage modes were observed, including light fiber tear failure, adhesive failure, and thin layer cohesive failure modes.